2005
DOI: 10.1159/000088898
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Selected Oral Microorganisms to Emit Red Fluorescence

Abstract: Some novel caries detection and excavation devices rely on the ability of bacteria to produce red fluorescing compounds. The aim of this study was to examine the ability of selected oral microorganisms to emit red fluorescence. Streptococcus mutans, S. oralis, S. salivarius, S. sobrinus, Lactobacillus fermentans, L. casei, L. rhamnosus, Actinomyces naeslundi, A. israelii, Prevotella intermedia, and Fusobacterium nucleatum were inoculated onto Columbia agar with haemin and vitamin K and incubated anaerobically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 35 publications
(24 reference statements)
6
66
0
16
Order By: Relevance
“…7 The first reports on this issue have focused on the red fluorescence produced by some anaerobic species of microorganisms cultured in the laboratory, such as some species of Actinomyces and microorganisms associated with periodontal disease. 3,11 Regarding dental caries, species of streptococci did not exhibit red fluorescence, 3,5,11 but various species of Lactobacilli emitted fluorescence at the red spectrum. 11 Recently, a research observed that microorganisms related to dental caries, including Streptococcus mutans, Lactobacillus salivarius, and Bifidobacterium dentium, produced red fluorescence when some nutrients were added to the growth media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The first reports on this issue have focused on the red fluorescence produced by some anaerobic species of microorganisms cultured in the laboratory, such as some species of Actinomyces and microorganisms associated with periodontal disease. 3,11 Regarding dental caries, species of streptococci did not exhibit red fluorescence, 3,5,11 but various species of Lactobacilli emitted fluorescence at the red spectrum. 11 Recently, a research observed that microorganisms related to dental caries, including Streptococcus mutans, Lactobacillus salivarius, and Bifidobacterium dentium, produced red fluorescence when some nutrients were added to the growth media.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that obligate anaerobic bacteria were the main source of red fluorescence, including microorganisms usually present in thicker plaque and in dentin caries lesions. 3,11 The subsequent studies investigated the red fluorescence emitted by the dental plaque, evaluating whether the interactions among the microorganisms could have some influence on it. It was observed that combinations of some bacterium were more associated with the emission of red fluorescence than the individual species of microorganisms, 6 and that this phenomenon is supposed to be related to the maturity of the dental plaque.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of RF is also used as indicator when a cavity preparation is clean. 43,44 Current research on RF focuses mainly on bacteria that could be a source for this RF and bacteria interactions and growth conditions. 10,43,45,46 Recently a more clinical approach is found in research of RF in relation to gingivitis, where not the red or GF of the teeth is the object of study but the RF seen from the subgingival plaque growing under the gums.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Studies have suggested that obligate anaerobic bacteria are the source of red fluorescence emission and especially the black pigmented e.g. Prevotella intermedia and Porphyromonas gingivalis [3,5,6,8,9]. In addition the majority of these studies havealso suggested that the red fluorescence emission not is directly caused by a single bacterium species, but "by the intrinsic characteristics of a mature biofilm" [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Red fluorescence emission has been demonstrated from Actinomyces odontolyticus, Actinomyces naeslundi, Actinomyces israelii and Prevotella intermedia present in cell cultures associated with dental caries, periodontal disease and dental plaque [3,[5][6][7]. Red fluorescence has also been obtained from the black-pigmented obligate anaerobes Porphyromonas gingivalis, P. intermedia, Prevotella melaninogenica, as well as from A. israelii [8].…”
Section: Introductionmentioning
confidence: 99%